A diaphragm and its preparation method and application

By coating the lithium-ion battery separator with inorganic adhesive and inorganic particles on the "grass-like" whisker group structure formed by inorganic adhesives and inorganic particles, the problem of insufficient heat resistance under high temperature conditions is solved, and the stability and safety of the separator at high temperatures is achieved.

CN119208914BActive Publication Date: 2025-03-28SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411709923.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators are insufficient in heat resistance under high temperature conditions, which easily melt and cause battery short circuit and thermal runaway, making it difficult to meet the safety requirements of large-capacity high-energy density lithium-ion batteries.

Method used

A coating consisting of inorganic adhesives and inorganic particles is adopted. The coating contains crystals formed from inorganic adhesives. Some crystals form needle-shaped whiskers, and the remaining crystals are located between the inorganic particles to form a "grass-like" structure to enhance the heat resistance of the separator.

Benefits of technology

Through the formation of "grass-like" whisker groups, the diaphragm can effectively suppress shrinkage, maintain integrity at high temperatures, and show excellent thermal protection effects, ensuring safe and efficient operation of the battery under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208914B_ABST
    Figure CN119208914B_ABST
Patent Text Reader

Abstract

The present invention discloses a diaphragm and a preparation method and application thereof, belonging to the technical field of battery materials. The diaphragm comprises a base film and a coating applied to at least one side of the base film; the coating comprises an inorganic adhesive and inorganic particles; the coating contains crystals formed by the inorganic adhesive; the crystals at least include needle-shaped whiskers, some of the crystals together form a whisker group, and the remaining crystals are located between the inorganic particles; the inorganic adhesive comprises M2O·nSiO2 whose mass is 1% to 35% of the mass of the inorganic particles in the coating, and M comprises at least one of Na, K and Li, and 1≤n≤4. The above-mentioned diaphragm has good stability and durability at high temperature, and the diaphragm has high peel strength, wettability, ionic conductivity, puncture strength and air permeability, which can ensure that the battery can still operate safely and efficiently under high temperature conditions. The preparation method of the diaphragm is simple, easy to prepare on an industrial scale, and has a good industrial prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a diaphragm and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high operating voltage, high energy density, long cycle life, small size, light weight, fast charging and environmental protection. They have developed rapidly in recent years and are widely used in portable electronic products, new energy vehicles and other fields. However, while the lithium battery industry is developing rapidly, the safety performance of lithium-ion batteries must also be considered.

[0003] Lithium-ion batteries are mainly composed of four parts: positive electrode, negative electrode, electrolyte and diaphragm. The diaphragm is mainly used to separate the positive and negative electrodes of lithium-ion batteries, prevent direct contact between the positive and negative electrodes, and provide a transmission channel for lithium ions while blocking the passage of electrons to prevent the battery from short-circuiting. The performance of the diaphragm has a great influence on the interface structure and internal resistance of lithium-ion batteries, and will directly affect the electrochemical performance and safety of lithium-ion batteries. When the battery is short-circuited or overcharged, a large amount of heat will be released, resulting in heat accumulation and temperature rise. Therefore, when the temperature rises, a diaphragm with high thermal stability can ensure that it has good dimensional integrity to effectively block direct contact between the positive and negative electrodes.

[0004] At present, battery separators are usually based on polyethylene (PE) and polypropylene (PP). This type of battery separator has insufficient heat resistance and will soften and deform above 130°C. Under conditions such as overcharge, over-discharge, rapid charge and discharge, abuse or high temperature, the separator is easy to melt and break, resulting in a short circuit in the battery, which leads to thermal runaway, causing the battery to catch fire or even explode, making it difficult to meet the strict safety requirements of large-capacity and high-energy-density lithium-ion batteries. In addition, the surface energy of polyethylene and polypropylene is low, and the wettability with the electrolyte is poor, resulting in the inability of the separator pores to be completely filled with electrolyte, which also affects the battery performance.

[0005] In order to improve the wettability and heat resistance of the diaphragm, the surface of the diaphragm can be modified by coating. For example, inorganic particles, adhesives, solvents and other additives can be prepared into a slurry and coated on the surface of the base film. However, the coating of the diaphragm currently has problems such as easy powdering and falling off. Especially in high temperature environments, the inorganic particle layer of the inorganic coated diaphragm is prone to powdering and breaking, causing the diaphragm to collapse, and it is impossible to effectively suppress the occurrence of thermal runaway, and it is difficult to ensure that the battery can still operate safely and efficiently under high temperature conditions.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The object of the present invention is to provide a diaphragm and a preparation method and application thereof, so as to solve or improve the above-mentioned technical problems.

[0008] The present invention can be implemented like this:

[0009] In a first aspect, the present invention provides a diaphragm, the diaphragm comprising a base film and a coating coated on at least one side of the base film; the coating comprising an inorganic adhesive and inorganic particles;

[0010] The coating contains crystals formed by an inorganic adhesive; the crystals include at least needle-shaped whiskers, some of the crystals together form a whisker group, and the remaining crystals are located between the inorganic particles;

[0011] The inorganic adhesive includes a component with a chemical formula of M2O·nSiO2, wherein M includes at least one of Na, K and Li, and 1≤n≤4; the mass of the component with a chemical formula of M2O·nSiO2 is 1% to 35% of the mass of the inorganic particles in the coating.

[0012] In an optional embodiment, the crystal has at least one of the following characteristics:

[0013] Feature 1: The crystals also include at least one of plate-like crystals and spherical crystals;

[0014] Feature 2: The diameter of the whiskers is 40nm~900nm;

[0015] Feature 3: The longest length of the whisker group is 1μm~20μm;

[0016] Feature 4: The whiskers are in a "grass-like" shape.

[0017] In an alternative embodiment, the diameter of the whisker is 50 nm to 600 nm. In an alternative embodiment, the longest length of the whisker group is 5 μm to 11 μm.

[0018] In an optional embodiment, the longest distance between any two points on the surface of the plate-like crystal is 1 μm to 3 μm.

[0019] In an optional embodiment, the longest distance between any two points on the surface of the spherical crystal is 1 μm to 3 μm.

[0020] In an optional embodiment, the mass of the component with the chemical formula M2O·nSiO2 is 1-20% of the mass of the inorganic particles in the coating, preferably 1-12%.

[0021] In an optional embodiment, the average particle size of the inorganic particles is 10 nm to 5 μm, preferably 11 nm to 4.9 μm.

[0022] In an optional embodiment, the inorganic particles include at least one of Al2O3, SiO2, BaSO4, BaO, titanium dioxide, MgO, LiF, MgF2, BaF2, CuO, Mg(OH)2, LiAlO2, ZrO2, carbon nanotubes, SiC, Si3N4, Fe2O3, BaTiO3, MoS2, α-V2O5, PbTiO3, TiB2, CaSiO3, molecular sieves, clay, boehmite and kaolin, and preferably include at least one of Al2O3, boehmite, SiO2 and BaTiO3.

[0023] In an optional embodiment, the thickness of the separator is 2.3 μm to 48 μm, preferably 3 to 45 μm, and more preferably 12 μm to 35 μm.

[0024] In an optional embodiment, the thickness of the base film is 2 μm to 40 μm, preferably 3 μm to 39 μm, and more preferably 12 μm to 28 μm.

[0025] In an optional embodiment, the thickness of the coating is 0.3 μm to 9 μm, preferably 0.4 μm to 8 μm, and more preferably 1.2 μm to 5 μm.

[0026] In an alternative embodiment, the base film includes at least one of a polymer base film and a ceramic base film.

[0027] In an optional embodiment, the polymer base film includes at least one of a polyamide base film, a polyimide base film, a polyolefin base film, a polyacrylonitrile base film, a cellulose base film, a polyester base film, a nanofiber nonwoven base film, and an aramid base film.

[0028] In a second aspect, the present invention provides a method for preparing a diaphragm as described in any of the aforementioned embodiments, comprising the following steps: coating a coating slurry containing an inorganic adhesive and inorganic particles on at least one surface of a base film, and drying.

[0029] In an optional embodiment, the solid content of the coating slurry is 2% to 50%, preferably 6% to 48%, and more preferably 20% to 43%.

[0030] In an optional embodiment, the viscosity of the coating slurry is 10 cp~1000 cp, preferably 20 cp~350 cp, and more preferably 20 cp~100 cp.

[0031] In an optional embodiment, the drying temperature is 50° C. to 70° C., and / or the drying time is 2 min to 5 min.

[0032] In a third aspect, the present invention provides a lithium ion battery, comprising the separator of any one of the aforementioned embodiments.

[0033] The beneficial effects of the present invention include:

[0034] The present invention arranges a coating including an inorganic adhesive and inorganic particles on at least one side of the base film. The coating contains crystals formed by the inorganic adhesive, and the crystals include at least needle-shaped whiskers. Some crystals together form a whisker group, and the remaining crystals are located between the inorganic particles.

[0035] The whisker groups in the above coatings are "rooted" in the coatings and "pin" the moving shrinkage interface at high temperatures, playing a "pinning effect" in the diaphragm, which can effectively inhibit the shrinkage of the diaphragm; in addition, the crystals located between the inorganic particles can form a network, so that the coating as a whole has the characteristics of continuous self-support, so that the coating can still maintain good integrity at high temperatures and when the base film is melted, without breaking or powdering, and exhibiting excellent thermal protection effects.

[0036] The diaphragm with the above characteristics has good stability and durability at high temperatures, and the diaphragm also has high peel strength, wettability, ionic conductivity, puncture strength and air permeability, which can ensure that the battery can still operate safely and efficiently under high temperature conditions.

[0037] The preparation method of the diaphragm provided by the invention is simple, easy to prepare on an industrial scale, and has a good industrial prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0039] Figure 1 This is a SEM image of the surface of a certain area of ​​the diaphragm (denoted as 2NSO5-22) prepared in Example 3;

[0040] Figure 2 for Figure 1 The enlarged view of the SEM results in the first box (in order from top to bottom);

[0041] Figure 3 for Figure 1 The enlarged view of the SEM results in the second box (from top to bottom);

[0042] Figure 4 This is a SEM image of the surface of another area of ​​the diaphragm (denoted as 2NSO5-22) prepared in Example 3;

[0043] Figure 5This is a SEM image of the surface of a certain area of ​​the diaphragm (denoted as 2NSO5-30) prepared in Example 5;

[0044] Figure 6 for Figure 5 A magnified view of the SEM results in the box;

[0045] Figure 7 for Figure 6 A magnified view of the SEM results in the box;

[0046] Figure 8 This is a SEM image of the surface of a certain area of ​​the diaphragm (denoted as 2NSO10-22) prepared in Example 6;

[0047] Fig. 9 This is a SEM image of the surface of a certain area of ​​the diaphragm (denoted as 2NSO20-22) prepared in Example 7;

[0048] Fig.10 This is a SEM image of the surface of another area of ​​the diaphragm prepared in Example 7;

[0049] Fig.11 This is a SEM image of the surface of a certain area of ​​the diaphragm (denoted as NSO5-22) prepared in Example 11;

[0050] Fig.12 for Fig.11 A magnified view of the SEM results in the box;

[0051] Fig.13 This is a SEM image of the surface of another area of ​​the diaphragm prepared in Example 11;

[0052] Fig.14 for Fig.13 A magnified view of the SEM results in the box;

[0053] Fig.15 This is a SEM image of a cross section of the diaphragm prepared in Example 4 after being kept at 130° C. for 1 hour;

[0054] Fig.16 This is a SEM image of a cross section of the diaphragm prepared in Example 3 after being kept at 200°C for 1 hour. DETAILED DESCRIPTION

[0055] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0056] The following is a detailed description of the diaphragm provided by the present invention and its preparation method and application.

[0057] The invention provides a diaphragm, which comprises a base film and a coating layer coated on at least one side surface of the base film; the coating layer comprises an inorganic adhesive and inorganic particles.

[0058] In some optional embodiments, the coating may be applied on the surface of any one side of the base film; in other optional embodiments, the coating may be applied on the surface of both sides of the base film.

[0059] The inorganic particles in the coating have a high specific surface area (e.g. 10m 2 / g~88m 2 / g) and good hydrophilicity, and has excellent wettability to organic electrolytes, especially to carbonate solvents with high dielectric constants and difficult to be wetted by polyolefin membranes. In addition, inorganic particles also have excellent temperature resistance and non-flammable and refractory properties, which are conducive to making the diaphragm have good temperature resistance and mechanical properties. However, the coating containing inorganic particles currently has problems such as easy powder loss, shedding, powderization and breakage. The important reason for the above defects is that the adhesive used in the coating containing inorganic particles is usually an organic adhesive. Organic adhesives have a significant problem of easy swelling in the electrolyte. Once the electrolyte is absorbed, it is easy to cause the performance of the battery core to decline. In addition, organic adhesives are unstable at high temperatures, easy to melt or decompose, resulting in the failure of their bonding with inorganic ceramic particles. Based on this, the present invention eliminates the traditional organic adhesive in the coating and adopts an inorganic adhesive. The inorganic adhesive is not easy to swell in the electrolyte, has low cost, simple operation, good bonding effect and is environmentally friendly. In addition, inorganic adhesives can overcome the defect of unstable performance of organic adhesives at high temperatures and exhibit excellent high temperature resistance.

[0060] However, not all inorganic adhesives are suitable for the present invention. The coating of the present invention contains crystals formed by the inorganic adhesive; some of the crystals together form a whisker group, the crystals at least include needle-shaped whiskers, and the remaining crystals are located between the inorganic particles.

[0061] The diameter of the whiskers is 40nm to 900nm, and the longest length of the whisker group is 1μm to 20μm.

[0062] It should be noted that the diameter of the whisker and the longest length of the whisker group can be measured by scanning electron microscopy. Among them, the whisker is a special crystal form, which is a fibrous crystal grown from high-purity raw materials. The diameter of the whisker can be understood as the width value relative to the whisker length. The diameter of crystals of other shapes can be understood as the maximum value obtained by comparing the shortest distance between any two points on the surface of the crystal.

[0063] In some optional embodiments, the crystals further include at least one of plate-like crystals and spherical crystals. It can be understood that: in some embodiments, the crystals may contain only needle-like whiskers; in other embodiments, the crystals may contain both needle-like whiskers and plate-like crystals; in other embodiments, the crystals may contain both needle-like whiskers and spherical crystals; in other embodiments, the crystals may contain both needle-like whiskers, spherical crystals and plate-like crystals.

[0064] In some optional embodiments, the diameter of the whiskers can be 50nm~600nm, such as 50nm, 70nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm or 600nm, etc., or it can be any value or any range within the range of 50nm~600nm.

[0065] In some optional embodiments, the longest length of the whisker group can be 5μm~11μm, such as 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm or 11μm, etc., or it can be any value or any range within the range of 5μm~11μm.

[0066] In some alternative embodiments, the whisker population may be in a "brush-like" configuration.

[0067] In some optional embodiments, the longest distance between any two points on the surface of the plate-like crystal is 1 μm to 3 μm.

[0068] In some optional embodiments, the longest distance between any two points on the surface of the spherical crystal is 1 μm to 3 μm.

[0069] As for the scheme of the present invention, during the drying and dehydration process of the diaphragm, the inorganic adhesive in the coating will crystallize. The crystallization stage is the hardening process of the inorganic adhesive. At this time, the gel body is transformed into crystals. Crystals in some areas gradually grow, intersperse between the coatings, overlap each other, and cross-climb to transform the gel into a three-dimensional space firmly combined and dense "grass-like" whisker group; the other part is located (for example, evenly dispersed) between the inorganic particles, interlaced with each other to form a network support. The whiskers in the coating are tightly combined with the inorganic particles to form a "reinforced concrete" structure.

[0070] The heat resistance of the diaphragm in the present invention is related to the whiskers grown in the coating. The "grass-like" whisker group is "rooted" in the coating and "pins" the moving shrinkage interface at high temperatures, playing a "pinning effect" in the diaphragm and effectively inhibiting the shrinkage of the diaphragm. In addition, the dispersed high-temperature resistant inorganic whiskers form a network, so that the coating as a whole has the characteristics of continuous self-support, so that the coating can still maintain good integrity at high temperatures and when the base film is melted, without breaking or powdering, and exhibiting excellent thermal protection effects.

[0071] In an optional embodiment, the inorganic adhesive includes a component with a chemical formula of M2O·nSiO2, wherein M includes at least one of Na, K and Li, and 1≤n≤4.

[0072] The component with the chemical formula M2O·nSiO2 is an inorganic compound composed of metal cations and polymer silicate anions. Wherein n represents the number of SiO2 units in the polymer anion, which is called modulus, n=SiO2 / M2O (molar ratio). In the present invention, the value of n can be 1, 1.5, 2, 2.5, 3, 3.5 or 4.

[0073] The outer electron configuration of the silicon atom of the inorganic adhesive used in the present invention is 3s 2 3p 2 , which has the property of heating dehydration polymerization. As the temperature of the liquid inorganic adhesive increases, the water in the inorganic adhesive evaporates, the silicate anions aggregate into a film, and more silanol groups are produced. The adjacent silanol groups condense to form Si-O-Si bonds, and the remaining water molecules continue to catalyze the dehydration condensation of the silanol groups. The viscosity of the adhesive continues to increase, and finally a three-dimensional network structure connected by Si-O-Si bonds is formed. This structure has strong bonding properties.

[0074] The value of the modulus n in the inorganic adhesive will affect the bonding performance of the inorganic adhesive. The larger the modulus, the stronger the bonding force, the easier it is to harden into a film, and the heat resistance of the diaphragm and the peel strength of the coating will also increase with the increase of the modulus n; but if the value of the modulus n is too large, not only will the viscosity of the inorganic adhesive increase, the operability will deteriorate, but it will also cause the proportion of cations to decrease, resulting in a decrease in ionic conductivity. Based on this, the present invention specifically uses an inorganic adhesive with n of 1 to 4.

[0075] The cation in the inorganic adhesive of the present invention is selected from at least one of Na, Li and K, which are light in weight and small in ionic radius. On the one hand, it is beneficial to improve the energy density and ion mobility of the material. On the other hand, it can avoid the harm of using magnetic elements such as Fe, Cr or Ni or other heavy metal elements to the battery or the environment. In some typical embodiments, M is at least one of Na and Li.

[0076] In some optional embodiments, the mass of the component with the chemical formula M2O·nSiO2 is 1% to 35% of the mass of the inorganic particles in the coating, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%, etc., and can also be other values ​​within the range of 1% to 35%. In some more typical embodiments, the mass of the component with the chemical formula M2O·nSiO2 is 1% to 20% of the mass of the inorganic particles in the coating; in some more typical embodiments, the mass of the component with the chemical formula M2O·nSiO2 is 1% to 12% of the mass of the inorganic particles in the coating.

[0077] The more inorganic adhesive is contained in the coating, the larger the whiskers contained in the coating. In addition, the modulus of the inorganic adhesive will also affect the size of the whiskers. The higher the modulus, the larger the diameter of the "grass-like" whisker group and the dispersed whiskers, and the better the heat resistance of the corresponding diaphragm. In addition, setting the mass of the component with the chemical formula M2O·nSiO2 within the above range can not only avoid the problem of low bonding strength caused by too little addition, but also avoid excessive addition causing rapid agglomeration of slurry particles, thereby causing membrane surface leakage, uneven coating thickness, shrinkage and curling, etc.

[0078] By combining the inorganic adhesive with the above characteristics with inorganic particles, the inorganic particles can be used as a curing agent for the inorganic adhesive. The inorganic particles and the inorganic adhesive can form a network structure through hydrogen bonds, van der Waals forces and their own bonding to achieve good bonding. Even under high temperature conditions, they will not melt or decompose, and can maintain their own size and structure well, which is beneficial to improving the performance of the battery.

[0079] In some optional embodiments, when the component with the chemical formula M2O·nSiO2 accounts for 5% of the mass of the inorganic particles in the coating, the diameter of the whiskers is 50nm~415nm, such as 50nm, 70nm, 80nm, 90nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 320nm, 340nm, 360nm, 380nm, 400nm or 415nm, etc., or it can be any value or any range within the range of 50nm~415nm.

[0080] In some optional embodiments, when the component with the chemical formula M2O·nSiO2 accounts for 20% of the mass of the inorganic particles in the coating, the diameter of the whiskers is 300nm~600nm, such as 300nm, 320nm, 340nm, 360nm, 380nm, 400nm, 420nm, 440nm, 460nm, 480nm, 500nm, 520nm, 540nm, 560nm, 580nm or 600nm, etc., or it can be any value or any range within the range of 300nm~600nm.

[0081] In some optional embodiments, the average particle size of the inorganic particles can be 10nm~5μm, such as 10nm, 20nm, 50nm, 80nm, 100nm, 200nm, 500nm, 800nm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 3.2μm, 3.5μm, 3.8μm, 4μm, 4.2μm, 4.5μm, 4.8μm or 5μm, etc., or any value or any range within the range of 10nm~5μm. In some typical embodiments, the average particle size of the inorganic particles is 11nm~4.9μm.

[0082] In some optional embodiments, the inorganic particles may exemplarily but not limitatively include at least one of Al2O3 (including α-type, β-type and / or γ-type, etc.), SiO2, BaSO4, BaO, titanium dioxide (including TiO2, rutile and / or anatase, etc.), MgO, LiF, MgF2, BaF2, CuO, Mg(OH)2, LiAlO2, ZrO2, carbon nanotubes (CNT), SiC, Si3N4, Fe2O3, BaTiO3, MoS2, α-V2O5, PbTiO3, TiB2, CaSiO3, molecular sieves (such as ZSM-5, etc.), clay, boehmite and kaolin. In some more typical embodiments, the inorganic particles may include at least one of Al2O3, boehmite, SiO2 and BaTiO3.

[0083] In some optional embodiments, the thickness of the diaphragm can be 2.3 μm to 48 μm, such as 2.3 μm, 2.5 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm, 40 μm, 42 μm, 45 μm or 48 μm, etc., or any value or any range within the range of 2.3 μm to 48 μm. In some more typical embodiments, the thickness of the diaphragm is 3 μm to 45 μm; in some more typical embodiments, the thickness of the diaphragm is 12 μm to 35 μm.

[0084] In some optional embodiments, the thickness of the base film can be 2 μm to 40 μm, such as 2 μm, 2.3 μm, 2.5 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm or 40 μm, etc., or any value or any range within the range of 2 μm to 40 μm. In some more typical embodiments, the thickness of the base film is 3 μm to 39 μm; in some more typical embodiments, the thickness of the base film is 12 μm to 28 μm.

[0085] In some optional embodiments, the thickness of the coating can be 0.3μm~9μm, such as 0.3μm, 0.5μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 3.2μm, 3.5μm, 3.8μm, 4μm, 4.2μm, 4.5μm, 4.8μm, 5μm, 5.2μm, 5.5μm, 5.8μm, 6μm, 6.2μm, 6.5μm, 6.8μm, 7μm, 7.2μm, 7.5μm, 7.8μm, 8μm, 8.2μm, 8.5μm, 8.8μm or 9μm, etc., or it can be any value or any range within the range of 0.3μm~9μm. In some typical embodiments, the thickness of the coating is 0.4 μm to 8 μm; in some more typical embodiments, the thickness of the coating is 1.2 μm to 5 μm.

[0086] If the thickness of the coating is less than 0.3μm, it will easily lead to a decrease in the thermal dimensional stability, liquid retention rate and capacity retention rate of the diaphragm; if the thickness of the coating is higher than 9μm, it will increase the difficulty of coating, and at the same time, the liquid retention rate of the electrolyte and the mass of the diaphragm will increase, resulting in a decrease in the energy density of the battery.

[0087] With the increase of M2O·nSiO2 content and coating thickness, the heat resistance of the separator is better and the peel strength of the coating is higher. The reason is that as the M2O·nSiO2 content increases, the interaction between the adhesive and the inorganic particles will also increase, and the adhesive and the inorganic particles will be more tightly bound; the increase in thickness is equivalent to increasing the content of adhesive and inorganic particles per unit area, which is beneficial to improve the bonding strength between the inorganic particles and the base film, inhibit the shrinkage of the separator at high temperature, and improve the heat resistance of the separator. In addition, with the increase of M2O·nSiO2 content and thickness in the coating, the ionic conductivity of the separator increases, which may be attributed to the difficulty of wetting the base film, resulting in poor electrolyte retention and absorption rate, while the porous structure in the coating and the good lyophilicity of the inorganic particles can increase the wettability of the separator. The good wettability of the separator can not only effectively shorten the electrolyte filling time during the battery assembly process, but also improve the electrolyte retention capacity, which is more conducive to the effective transmission of ions during the battery operation. The thicker the coating, the more electrolyte liquid is retained and absorbed, and the more inorganic adhesive content increases the conductive ion content, which will increase the ionic conductivity of the diaphragm. However, too high a coating thickness will increase the ion transmission distance and reduce the ionic conductivity. Therefore, the coating thickness needs to be reasonably controlled according to demand. In addition, when the content of inorganic adhesive is too high, not only is the slurry difficult to coat, but it will also cause the coating slurry to agglomerate rapidly, the particle size will increase significantly, the slurry stability will deteriorate, and the coating will leak.

[0088] In some optional embodiments, the base film includes at least one of a polymer base film and a ceramic base film. The polymer base film may exemplarily but not limitatively include at least one of a polyamide base film, a polyimide base film, a polyolefin base film (wherein the polyolefin may include polyethylene, polypropylene, polyvinylidene fluoride and / or polytetrafluoroethylene, etc.), a polyacrylonitrile base film, a cellulose base film, a polyester base film (wherein the polyester may include polyethylene terephthalate, etc.), and an aramid base film. In addition, other lithium-ion battery base films may also be used according to actual needs.

[0089] In some optional embodiments, the base film can be in a single-layer form, a double-layer form, or a multi-layer form. When the number of base film layers is 2 or more, the material of each base film layer can be the same or different, and similarly, the thickness of each base film layer can be equal or different. When the number of base film layers is 2 or more, each layer can be combined together by coextrusion and / or lamination.

[0090] As mentioned above, the diaphragm provided by the present invention has good stability and durability at high temperatures, and the diaphragm also has high peel strength, wettability, ionic conductivity, puncture strength and air permeability, which can ensure that the battery can still operate safely and efficiently under high temperature conditions.

[0091] Correspondingly, the present invention also provides a method for preparing the above-mentioned diaphragm, comprising the following steps: coating a coating slurry containing an inorganic adhesive and inorganic particles on at least one surface of the base film, and drying.

[0092] The coating may be exemplarily but not limitatively carried out by electrostatic spraying, blade coating, extrusion coating, transfer coating, dip coating, gravure or micro-gravure coating, as long as the coating slurry can be coated on the surface of the base film.

[0093] In some optional embodiments, the solid content of the coating slurry can be 2% to 50%, such as 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48% or 50%, etc., or any value or any range within the range of 2% to 50%. In some more typical embodiments, the solid content of the coating slurry is 6% to 48%; in some more typical embodiments, the solid content of the coating slurry is 20% to 43%.

[0094] In some optional embodiments, the viscosity of the coating slurry can be 10cp~1000cp, such as 10cp, 20cp, 50cp, 80cp, 100cp, 200cp, 500cp, 800cp or 1000cp, etc., or any value or any range within the range of 10cp~1000cp. In some more typical embodiments, the viscosity of the coating slurry is 20cp~350cp; in some more typical embodiments, the viscosity of the coating slurry is 20cp~100cp.

[0095] The coating slurry is obtained by mixing the raw materials for preparing the coating with a solvent, and the solvent may be water, for example.

[0096] The raw materials for preparing the coating include inorganic adhesives and inorganic particles, and further, may include at least one of a thickener, a dispersant, a flame retardant and a wetting agent.

[0097] The mass of the thickener may be 0.5-5% of the mass of the inorganic particles, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or any value or range within the range of 0.5-5%. The thickener may exemplarily but not limitatively include carboxymethyl cellulose (CMC) and the like.

[0098] The mass of the dispersant can be 0.2-5% of the mass of the inorganic particles, such as 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or any value or any range within the range of 0.2-5%. The dispersant can exemplarily but not limitatively include at least one of polyacrylamide, sodium hexametaphosphate and methylpentanol.

[0099] The mass of the flame retardant can be 1-5% of the mass of the inorganic particles, such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or any value or any range within the range of 1-5%. The flame retardant can exemplarily but not limitatively include at least one of brominated flame retardant, ammonium phosphate, ammonium hydroxide, aluminum trihydrate and phosphate ester.

[0100] The mass of the wetting agent can be 0.05-5% of the mass of the inorganic particles, such as 0.05%, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or any value or any range within the range of 0.05-5%. The wetting agent can exemplarily but not limitatively include at least one of ethanol, propylene glycol, glycerol, polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, fatty acid ester sulfate and vinyl triethoxysilane.

[0101] In some optional embodiments, the drying temperature may be 50°C to 70°C, such as 50°C, 55°C, 60°C, 65°C or 70°C, etc., or any value or any range within the range of 50°C to 70°C.

[0102] The drying time may be 2 min to 5 min, such as 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min or 5 min, etc., or may be any value or any range within the range of 2 min to 5 min.

[0103] Drying conditions will affect the crystals. At the beginning of drying, the water in the adhesive evaporates, anions gather into a film, and more silanol groups are produced. The water molecules in the adhesive rearrange, catalyzing the condensation between adjacent silanol groups to form Si-O-Si bonds. As the temperature rises or the drying time increases, the remaining water molecules continue to catalyze the dehydration condensation of the silanol groups, and then a local reaction occurs on the surface of the dispersed anhydrous compound particles to form a gel, with a significant exothermic effect. The crystallization stage is the hardening process of the inorganic adhesive. At this time, the gel is transformed into crystals. The crystals gradually grow and overlap and cross-climb each other to transform the gel into a three-dimensional space that is firmly bonded and dense, accompanied by a small amount of heat release.

[0104] If the drying temperature is set too low, it will not only cause the problem of slow crystal growth rate, but also require extending the drying cycle to ensure that the diaphragm reaches the established moisture standard, reducing production efficiency. On the contrary, if the drying temperature is too high, it may cause the whiskers to grow less tightly and the crystal structure to tend to be loose, thereby weakening its mechanical properties. In addition, high-temperature drying will also increase the energy consumption of drying equipment, which will have an adverse effect on cost control. In terms of the regulation of drying time, too long drying time will cause the whisker size to increase abnormally, and it will also be accompanied by an increase in energy consumption, which is not conducive to cost control and hinders the improvement of production efficiency. If the drying time is too short, it is difficult to ensure that the moisture in the diaphragm meets the production standards.

[0105] In addition, the present invention also provides a lithium ion battery, which includes the above-mentioned separator.

[0106] Specifically, the lithium-ion battery comprises a positive electrode, a negative electrode and a separator, wherein the separator is used to separate the positive electrode from the negative electrode. The lithium-ion battery having the separator has good safety in use.

[0107] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0108] Example 1

[0109] This embodiment provides a diaphragm, which includes a base film and a coating layer coated on both sides of the base film.

[0110] The base film is a porous polyethylene (PE) with a thickness of 9 μm, the coatings on both sides of the base film are 2 μm thick, and the total thickness of the separator is 13 μm.

[0111] The coating slurry used to prepare the coating is obtained by dissolving the raw materials in water. The solid content of the coating slurry is 26.3% and the viscosity is about 20cp.

[0112] In terms of mass, the raw materials include 100 parts of inorganic particles (alumina powder with an average particle size of 500 nm), 5 parts of inorganic adhesive (Na2O·3SiO2), 1.5 parts of thickener (CMC), 0.5 parts of dispersant (polyacrylamide) and 0.1 parts of wetting agent (vinyl triethoxysilane).

[0113] The preparation method of the diaphragm comprises:

[0114] S1: According to the above-mentioned amount of raw materials, 100 parts of inorganic particles, 0.5 parts of dispersant and 1.5 parts of thickener were added to 300 parts of deionized water, and mechanically stirred at a speed of 2000 rpm for 4 hours to obtain a first slurry; the first slurry was fully ball-milled and evenly dispersed in a ball mill at a ball milling rate of 60 rpm for 24 hours to obtain a second slurry.

[0115] S2: Filter the second slurry, add 5 parts of inorganic adhesive and 0.1 parts of wetting agent to the filtered second slurry, and stir mechanically for 1 hour at a stirring speed of 500 rpm to obtain a coating slurry.

[0116] S3: The coating slurry is evenly coated on both sides of the base film on a coating machine, and vacuum dried at 60° C. for 5 minutes to obtain a diaphragm with coatings on both sides of the base film.

[0117] Example 2

[0118] The difference between this embodiment and embodiment 1 is that the amount of the inorganic adhesive is 2 parts, and the inorganic adhesive is Na2O·2SiO2.

[0119] Example 3

[0120] The difference between this embodiment and embodiment 2 is that the amount of the inorganic adhesive is 5 parts;

[0121] It can also be understood that the difference between this embodiment and embodiment 1 is that the inorganic adhesive is Na2O·2SiO2.

[0122] Example 4

[0123] The difference between this embodiment and embodiment 3 is that a coating layer of 2 μm is provided only on one surface of the base film.

[0124] Example 5

[0125] The difference between this embodiment and embodiment 4 is that the thickness of the coating is 3 μm;

[0126] It can also be understood that the difference between this embodiment and embodiment 1 is that a 3 μm coating is provided only on one surface of the base film.

[0127] Example 6

[0128] The difference between this embodiment and embodiment 2 is that the amount of the inorganic adhesive is 10 parts;

[0129] It can also be understood that the difference between this embodiment and embodiment 1 is that the inorganic adhesive is Na2O·2SiO2, and the amount of the inorganic adhesive is 10 parts.

[0130] Example 7

[0131] The difference between this embodiment and embodiment 2 is that the amount of inorganic adhesive is 20 parts;

[0132] It can also be understood that the difference between this embodiment and embodiment 1 is that the inorganic adhesive is Na2O·2SiO2, and the amount of the inorganic adhesive is 20 parts.

[0133] Example 8

[0134] The difference between this embodiment and embodiment 3 is that the inorganic adhesive is Na2O·1.5SiO2;

[0135] It can also be understood that the difference between this embodiment and embodiment 1 is that the inorganic adhesive is Na2O·1.5SiO2.

[0136] Example 9

[0137] The difference between this embodiment and Embodiment 8 is that a 2 μm coating is provided only on one surface of the base film.

[0138] Example 10

[0139] The difference between this embodiment and embodiment 9 is that a coating layer of 3 μm is provided only on one surface of the base film.

[0140] Embodiment 11

[0141] The difference between this embodiment and embodiment 3 is that the inorganic adhesive is Na2O·SiO2;

[0142] It can also be understood that the difference between this embodiment and embodiment 1 is that the inorganic adhesive is Na2O·SiO2.

[0143] Example 12

[0144] The difference between this embodiment and embodiment 11 is that the amount of the inorganic adhesive used is 10 parts.

[0145] Embodiment 13

[0146] The difference between this embodiment and embodiment 1 is that the inorganic adhesive is Na2O·4SiO2.

[0147] Embodiment 14

[0148] The difference between this embodiment and embodiment 1 is that the inorganic adhesive is K2O·3SiO2.

[0149] Embodiment 15

[0150] The difference between this embodiment and embodiment 1 is that the inorganic adhesive is Li2O·3SiO2.

[0151] Example 16

[0152] The difference between this embodiment and embodiment 1 is that: the inorganic particles are SiO2; the mass of Na2O·3SiO2 is 1% of the mass of the inorganic particles in the coating; the mass of the thickener is 0.5% of the mass of the inorganic particles; the mass of the dispersant is 0.2% of the mass of the inorganic particles; the mass of the flame retardant (ammonium phosphate) is 1% of the mass of the inorganic particles; the mass of the wetting agent is 0.1% of the mass of the inorganic particles; the thickness of the base film is 2μm, and the thickness of the coating on each side of the base film is 0.3μm. The solid content of the coating slurry is 2%, and the viscosity of the coating slurry is 10cp; the drying temperature is 50℃, and the drying time is 5min.

[0153] Embodiment 17

[0154] The difference between this embodiment and embodiment 1 is that: the inorganic particles are BaTiO3; the mass of Na2O·3SiO2 is 35% of the mass of the inorganic particles in the coating; the mass of the thickener is 5% of the mass of the inorganic particles; the mass of the dispersant is 5% of the mass of the inorganic particles; the mass of the flame retardant (alumina trihydrate) is 5% of the mass of the inorganic particles; the mass of the wetting agent is 5% of the mass of the inorganic particles; the thickness of the base film is 40μm, and the thickness of the coating on each side of the base film is 9μm. The solid content of the coating slurry is 50%, and the viscosity of the coating slurry is 1000cp; the drying temperature is 70℃, and the drying time is 2min.

[0155] Embodiment 18

[0156] The difference between this embodiment and embodiment 1 is that the mass of Na2O·3SiO2 is 12% of the mass of the inorganic particles in the coating. The inorganic particles are boehmite.

[0157] Embodiment 19

[0158] The difference between this comparative example and Example 1 is that the inorganic adhesive is Na2O·5SiO2.

[0159] Embodiment 20

[0160] The difference between this comparative example and Example 1 is that the mass of the inorganic adhesive is 40% of the mass of the inorganic particles in the coating.

[0161] Embodiment 21

[0162] The difference between this comparative example and Example 1 is that the thickness of the coating is 12 μm.

[0163] Comparative Example 1

[0164] The difference between this comparative example and Example 1 is that no coating is provided on the surface of the base film.

[0165] Comparative Example 2

[0166] The difference between this comparative example and Example 1 is that the inorganic adhesive is replaced by a polymethacrylic acid adhesive.

[0167] Comparative Example 3

[0168] The difference between this comparative example and Example 1 is that the inorganic adhesive is replaced by polyacrylamide adhesive.

[0169] Comparative Example 4

[0170] The difference between this comparative example and Example 1 is that the inorganic adhesive is aluminum sol.

[0171] Test example

[0172] (1) The performance of the diaphragms obtained in Examples 1 to 21 and Comparative Examples 1 to 4 was tested. The performance results are shown in Tables 1 and 2.

[0173] Performance test method reference:

[0174] ①. Shrinkage rate: Cut the diaphragm into multiple sizes of 120mm×100mm (length×width) in the longitudinal (MD) and transverse (TD) directions, cover the surface of the diaphragm with a piece of A4 paper, put it in an oven at 130°C, 150°C, and 200°C for 1 hour, measure the size of the direction after heat shrinkage, and calculate the shrinkage ratio. The shrinkage rate values ​​of the diaphragm in Table 1 are based on the average values ​​obtained in each direction after three measurements in the MD and TD directions.

[0175] ②. Peel strength: Test the peel strength between the coating and the base film on a universal tensile tester. Use a sampler to cut the coated membrane into a 150mm×30mm (length×width) sample strip, adhere it to the double-sided tape of the test plate, and then adhere a 200mm×20mm (length×width) transparent tape on top of the sample strip, and then use a cylindrical roller to naturally press the membrane in the same direction. When the membrane is coated on one side, the corresponding base film faces down and the coating faces up. Peel off one end of the transparent tape from the membrane coating surface until the adhesion length between the transparent tape and the membrane coating surface is 80mm, fold the free end of the transparent tape in half, clamp the free end of the transparent tape and the test plate on the upper and lower clamps respectively, and use a tensile tester in the same environment to continuously peel at a tensile speed of 100mm / min until the coating and the base film are completely separated, and directly read and record the membrane coating peel strength.

[0176] ③. Air permeability and puncture strength: refer to GBT36363-2018 standard; thickness is measured by Marr film thickness gauge.

[0177] ④. Water contact angle: Use contact angle measuring instrument according to GBT30693-2014 standard.

[0178] ⑤. Wettability of electrolyte: The wettability of the diaphragm is characterized by dripping electrolyte droplets on the surface of the diaphragm and measuring the size change of the droplets formed at 5 seconds and 5 minutes. Specifically, the droplet size is expressed by measuring the sum of the longest distances in the MD and TD directions divided by 2, and the droplet size corresponding to 5s and 5min is tested and the difference is divided by 2 to express the wettability.

[0179] ⑥. Ionic conductivity: Cut 5 diaphragms that match the resistance test mold, put the diaphragms into a 1 mol / L lithium hexafluorophosphate (LiPF6) electrolyte, the solvent of which is ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 1:1:1, and keep it sealed and soaked for 2 hours. Use an electrochemical workstation at 25°C, 0.01Hz~1×10 6 The electrochemical impedance spectrum is tested and recorded in the frequency range of Hz, with the number of diaphragm layers as the horizontal axis and the diaphragm resistance as the vertical axis. The slope and linear fit of the curve are calculated. When the linear fit is greater than 0.99, the slope (k) is the diaphragm impedance value, which can be calculated by the formula The ionic conductivity of the membrane is calculated as follows: is the ionic conductivity of the membrane, d is the diaphragm thickness, k is the diaphragm impedance value, S It is the area used during the diaphragm test.

[0180] ⑦. Slurry particle size: The prepared coating slurry is tested for particle size using Malvern laser particle size analyzer MS3000.

[0181] ⑧. Slurry stability time: Particle size D measured by Malvern laser particle size analyzer MS3000 50 Greater than 2μm time.

[0182] Table 1 Performance test results

[0183]

[0184] Table 2 Performance test results (continued)

[0185]

[0186] Combined with Table 1 and Table 2, the embodiments of the present invention use inorganic adhesives to replace traditional organic adhesives, and at the same time control the amount of inorganic adhesives and the modulus of inorganic adhesives, so that the prepared diaphragm has high ionic conductivity, good wettability and good high temperature resistance. In some preferred methods, under the conditions that the coating thickness is 4μm and the diaphragm thickness does not exceed 13μm, the shrinkage rate of heat treatment at 200℃ for 1h can be less than 3% and no powder falls off, indicating that the adhesive has not failed at this time, and the safety of the diaphragm is significantly improved, meeting the use requirements.

[0187] Comparing Examples 2 to 7 and Examples 9 to 10, it can be seen that as the amount of inorganic adhesive and the thickness of the coating increase, the heat resistance of the diaphragm is better and the peel strength of the coating is higher. This is because the increase in the amount of inorganic adhesive will intensify the interaction between the inorganic adhesive and the inorganic particles, and the inorganic adhesive and the inorganic particles will be more tightly bonded; the increase in coating thickness is equivalent to increasing the content of inorganic adhesive and inorganic particles per unit area, thereby increasing the bonding strength between the inorganic particles and the base film, inhibiting the shrinkage of the diaphragm at high temperatures, and improving heat resistance.

[0188] In addition, compared with the base film of Comparative Example 1, the ionic conductivity of the diaphragm provided in the above embodiment is significantly increased and increases with the increase of the amount of inorganic adhesive and the thickness of the coating. This can be attributed to the fact that the base film (PE) is difficult to wet, resulting in poor electrolyte retention and absorption rates, while the highly developed porous structure of the inorganic coating and the good lyophilic properties of the inorganic particles significantly increase the wettability of the diaphragm (the contact angle drops from 114° to below 14°). The good wettability of the diaphragm can not only effectively shorten the filling time of the electrolyte during the battery assembly process, but also improve the retention capacity of the electrolyte, which is more conducive to the effective transmission of ions during the operation of the battery. Moreover, the thicker the coating, the more electrolyte retention and absorption, and the more inorganic adhesive content will increase the content of conductive ions, all of which will increase the ionic conductivity of the diaphragm, but too high a coating thickness will increase the ion transmission distance and thus reduce the ionic conductivity. In addition, when the content of inorganic adhesive is too high, not only will the coating slurry be difficult to apply, but it will also cause the coating slurry to agglomerate rapidly, the particle size to increase significantly, the stability of the coating slurry to deteriorate, and lead to coating omissions and other phenomena.

[0189] From the results of Example 3, Example 8, Example 11 and Example 12, it can be seen that with the same thickness and inorganic adhesive content, the heat resistance of the diaphragm and the peel strength of the coating will increase with the increase of the modulus of the inorganic adhesive, but the increase in the modulus will reduce the proportion of cations, resulting in a slight decrease in ionic conductivity. In addition, Example 3 containing 5 parts of Na2O·2SiO2 has a lower shrinkage rate than Example 12 containing 10 parts of Na2O·SiO2 at the same temperature, indicating that the modulus of the inorganic adhesive has a greater impact on the heat resistance of the diaphragm.

[0190] It can be seen from Examples 1 and 19 to 21 that the modulus, dosage and coating thickness of the inorganic adhesive will affect the performance of the diaphragm. If the conditions are not set properly, the performance of the diaphragm will be reduced. Too high a modulus (such as Example 19) will reduce heat resistance, ionic conductivity and slurry stability. The more adhesive content, the larger the slurry particle size, the shorter the stabilization time, and exceeding a certain amount (such as Example 20) will cause leakage, resulting in a sharp deterioration in performance. Although increasing the thickness will improve heat resistance, it will also increase the permeability and reduce ionic conductivity, and will also reduce the volume energy density of the battery (such as Example 21).

[0191] Compared with Comparative Examples 2 and 3, all the separators obtained in the examples using inorganic adhesives with the same amount of organic adhesive and coating thickness as those in the two comparative examples have higher heat resistance, peel strength and ionic conductivity.

[0192] Compared with Comparative Example 4, the performance of the diaphragm obtained in Example 1 is more excellent, which means that even if inorganic adhesives are used, it is not always possible to obtain a diaphragm with excellent performance.

[0193] (2) The membranes obtained in various embodiments of the present invention were observed by scanning electron microscopy. The results showed that the coatings of the membranes prepared in the embodiments of the present invention contained crystals. Some of the crystals formed a group of "grass-like" whiskers, and the remaining crystals were located between the inorganic particles. The shapes of the crystals include needle-shaped, flake-shaped, and spherical; the diameters of the whiskers were in the range of 40nm to 900nm, and the longest length of the whisker group was in the range of 1μm to 20μm. The longest distance between any two points on the surface of the flake crystal and the longest distance between any two points on the surface of the spherical crystal were 1μm to 3μm.

[0194] Among them, the scanning electron microscope images of the diaphragms prepared in Examples 3, 5 to 7 and 11 are taken as examples. Figures 1 to 14 .

[0195] Depend on Figures 1 to 14 It can be seen that the coating of the diaphragm contains crystals, and the shapes of the crystals include needles, flakes and spheres. Figures 1 to 7 It can be seen that in some areas of the coating, the crystals are interspersed between the coatings and overlap and cross-climb each other, forming a "grass-like" whisker group that is firmly combined and dense in three-dimensional space; in some areas, the crystals are evenly dispersed between the inorganic particles, interlaced with each other to form a network support, and the whiskers between the coatings are tightly combined with the inorganic particles to form a "reinforced concrete" structure.

[0196] Moreover, as the amount of inorganic adhesive increases, the whiskers formed in the coating become larger. At the amount of inorganic adhesive corresponding to Example 3 (5 parts), the diameter of the whiskers formed in the coating is about 78nm~415nm; at the amount of inorganic adhesive corresponding to Example 7 (20 parts), the diameter of the whiskers formed in the coating is about 300nm~586nm, and the morphology is also changed compared with Example 3. The whiskers in Example 7 are flaky or spherical, and the main size of the whisker group (that is, the longest length of the whiskers) is mostly in the range of 5μm~11μm.

[0197] It can be seen from the SEM images corresponding to Example 3 and Example 11 that the modulus of the inorganic adhesive will affect the size of the whiskers. The higher the modulus, the larger the "grass-like" whisker group and the whisker diameter, and the better the heat resistance of the corresponding diaphragm, which further illustrates the influence of the size of the whiskers on the heat resistance of the diaphragm.

[0198] It should be noted that when the ceramic diaphragm is heated, the friction and adhesion between the ceramic layer and the base membrane layer, the gravity of the ceramic layer or the pressure applied during battery assembly will hinder the contraction and movement of the base membrane, making its structure intact and increasing its stability.

[0199] Fig.15 The SEM cross-sectional view of the diaphragm of Example 4 after being kept at 130°C for 1 hour shows that the pores of the base film and the structure of the ceramic particle layer can be kept intact at this temperature. At higher temperatures, the base film will melt and the pores will close, but the ceramic particles will be embedded in the base film to form an interlocking structure to make the diaphragm structure intact, avoid direct contact between the positive and negative electrodes, and inhibit further temperature increases, thereby improving the thermal safety of the diaphragm.

[0200] Fig.16 The SEM cross-sectional view of the diaphragm of Example 3 after being kept at 200°C for 1 hour shows that the molten base film is embedded in the gaps between the alumina particles to form an interlocking interface structure. The formation of this structure can significantly increase the contact area between the alumina particles and the base film, making the diaphragm structure complete and thus improving the thermal safety of the diaphragm.

[0201] (3) Taking Example 1, Example 3, Examples 6-8, Example 12 and Comparative Examples 1-3 as examples, the separators and positive and negative electrode sheets prepared in the above Examples and Comparative Examples were prepared into battery cells through a lamination process, and insulation breakdown short circuit resistance tests were performed, and the number of cells that passed the 250V voltage test was counted. The results are shown in Table 3.

[0202] Table 3 Insulation breakdown short circuit test results

[0203]

[0204] From the test results in Table 3, it can be seen that compared with the organic adhesive composite diaphragm with PE as the substrate and the PE diaphragm without inorganic coating, the diaphragm provided by the present invention has good insulation resistance, and the passing rate of the 250V breakdown short circuit test is more than 95%, while the passing rate of the PE diaphragm without inorganic coating is 79%, and the passing rate of the organic adhesive composite diaphragm with PE as the substrate does not exceed 90%. It can be seen that the diaphragm provided by the present invention can have higher insulation performance, which is conducive to improving the yield rate of the battery.

[0205] (4) Taking Example 1, Example 3, Examples 6 to 8, Example 12 and Comparative Examples 1 to 3 as examples, the separators and positive and negative electrode sheets prepared in the above Examples and Comparative Examples were prepared into battery cells through a lamination process, and then conventional lithium battery processes such as liquid injection, packaging, and formation were carried out. The safety performance of the completed batteries was tested, and the results are shown in Table 4.

[0206] 150℃ thermal shock pass rate: tested according to the national standard GB / T18287-2013 method, and the judgment criteria are no leakage, no fire, and no explosion.

[0207] Short circuit pass rate: tested according to the national standard GB / T18287-2013 method, the judgment criteria are no fire, no explosion, and the outer surface temperature is lower than 150℃.

[0208] 10V / 3C overcharge pass rate: tested according to the national standard GB / T18287-2013 method, and the judgment standard is no fire or explosion.

[0209] Table 4 Safety performance test results

[0210]

[0211] It can be seen from the test in Table 4 that the battery prepared by the diaphragm of the present invention has superiority in safety performance test compared with the organic adhesive composite diaphragm with PE as the substrate and the PE diaphragm without inorganic coating. The diaphragm provided by the present invention has a small thermal shrinkage rate at high temperature, which can give the battery good safety performance. When thermal runaway or improper use leads to accidents, it can more effectively avoid accidents such as battery fire and explosion.

[0212] In summary, the diaphragm provided by the present invention has good stability and durability at high temperatures, and can simultaneously have high peel strength, wettability, ionic conductivity, puncture strength and air permeability, which can ensure that the battery can still operate safely and efficiently under high temperature conditions. The preparation method of the diaphragm is simple and easy to prepare on an industrial scale, and has a good industrial prospect.

[0213] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A diaphragm, characterized in that: The diaphragm includes a base film and a coating layer coated on at least one side of the base film; the coating layer includes an inorganic adhesive and inorganic particles; The coating contains crystals formed by the inorganic adhesive; the crystals include at least needle-shaped whiskers, some of the crystals together form a whisker group, and the remaining crystals are located between the inorganic particles; The inorganic adhesive comprises a component having a chemical formula of M2O·nSiO2, wherein M comprises at least one of Na, K and Li, and 1≤n≤4; The mass of the component with the chemical formula of M2O·nSiO2 is 1% to 35% of the mass of the inorganic particles in the coating; The whisker group is in a "grass-like" shape.

2. The diaphragm according to claim 1, characterized in that The crystal has at least one of the following characteristics: Feature 1: The crystals also include at least one of plate-like crystals and spherical crystals; Feature 2: The diameter of the whisker is 40nm~900nm; Feature 3: The longest length of the whisker group is 1 μm to 20 μm.

3. The diaphragm according to claim 2, characterized in that The diameter of the whisker is 50nm~600nm; And / or, the longest length of the whisker group is 5 μm to 11 μm.

4. The diaphragm according to any one of claims 1 to 3, characterized in that: The average particle size of the inorganic particles is 10nm~5μm; And / or, the inorganic particles include at least one of Al2O3, SiO2, BaSO4, BaO, titanium dioxide, MgO, LiF, MgF2, BaF2, CuO, Mg(OH)2, LiAlO2, ZrO2, carbon nanotubes, SiC, Si3N4, Fe2O3, BaTiO3, MoS2, α-V2O5, PbTiO3, TiB2, CaSiO3, molecular sieves, clay, boehmite and kaolin.

5. The diaphragm according to any one of claims 1 to 3, characterized in that: The thickness of the diaphragm is 2.3 μm to 48 μm; And / or, the base film has a thickness of 2 μm to 40 μm; And / or, the coating has a thickness of 0.3 μm to 9 μm.

6. A method for preparing a diaphragm according to any one of claims 1 to 5, characterized in that: The following steps are involved: A coating slurry containing the inorganic adhesive and the inorganic particles is coated on at least one side of the base film and dried.

7. The preparation method according to claim 6, characterized in that: The solid content of the coating slurry is 2% to 50%; and / or the viscosity of the coating slurry is 10cp to 1000cp.

8. The preparation method according to claim 6 or 7, characterized in that: The drying temperature is 50°C to 70°C, and / or the drying time is 2min to 5min.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the separator according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Ultrathin shrinkage-resistant high-liquid-absorption and high-liquid-retention lithium battery diaphragm and preparation method thereof

    CN117712621A